Pengembangan E-LKPD Terintegrasi Case Method Dengan Sway App Pada Materi Sistem Peredaran Darah Manusia Kelas XI SMA: (Development of a Case Method-Based E-LKPD Integrated with Sway App on Human Circulatory System for Grade XI Senior High School Students) - Asia, Lady; Zulfarina, Zulfarina; Darmawati , Darmawati (BIODIK, 2025)
Digital teaching materials are highly needed by students. This study aims to produce a quality E-LKPD integrated with the case method and Sway App for the human circulatory system topic in Grade XI senior high school. The type of research used is Research and Development (R&D) with the ADDIE development model, which consists of the stages: Analyze, Design, Develop, Implement, and Evaluate. However, this study was limited only to the Develop stage. The data collected in this study were primary data obtained through validation questionnaires and trial response questionnaires. Based on the results, the average validation score was 3.42, categorized as very valid. The first trial stage yielded an average score of 3.86, and the second trial stage obtained a score of 3.36, both categorized as very good. The overall average score of 3.55 indicates that the E-LKPD integrated with the case method and Sway App has very good quality and is feasible for use as a digital teaching material on the human circulatory system topic for Grade XI senior high school students. Abstrak. Bahan ajar digital sangat dibutuhkan oleh peserta didik. Tujuan dalam penelitian ini yaitu untuk menghasilkan E-LKPD terintegrasi case method dengan sway app pada materi sistem peredaran darah manusia kelas XI SMA yang berkualitas. Jenis penelitian ini yaitu penelitian pengembangan Research and Development (R&D) dengan model ADDIE, terdiri dari tahapan Analyze, Design, Develop, Implement, Evaluate. Namun penelitian ini dibatasi hanya sampai tahap Develop. Pengambilan data penelitian ini adalah data primer berupa angket validasi dan angket respon uji coba. Berdasarkan hasil penelitian, didapatkan hasil rata-rata nilai validasi sebesar 3,42 dengan kategori sangat valid. Uji coba tahap I menghasilkan nilai rata-rata 3,86, dan tahap II memperoleh nilai sebesar 3,36, keduanya berkategori sangat baik. Rata-rata keseluruhan sebesar 3,55 menunjukkan bahwa E-LKPD terintegrasi case method dengan sway app memiliki kualitas sangat baik dan layak digunakan sebagai bahan ajar digital pada materi sistem peredaran darah manusia kelas XI SMA.